THE IMPACT OF FREE TRADE BETWEEN ASEAN AND CHINA ON THE INDONESIAN HOUSEHOLDS - Indra Maipita (Quantitative Economics Journal, 2014)
Free trade agreement between ASEAN and China was executed in early 2010. Various types of trade tariffs have been removed or lowered to support the agreement which may lead to changes in the welfare of Indonesian households. This research tries to find out the impact of ASEAN-China free trade agreement on the welfare of households in Indonesia. The model used for this analysis is AGEFIS model, a Computable General Equilibrium model of Indonesian economy. The findings of this research show that the free trade between ASEAN and China increases the level of economic activity. Various macroeconomic indicators such as output and exports increase relative to the output prior to the  free trade agreement. Income of urban households rise but rural households are adversely affected. Skilled-workers benefits more than unskilled ones.